Environmental Isotope of Radon-222 for Ciliwung River and Shallow Groundwater Interaction Study - Pujiindiyati, Evarista Ristin; Pratikno, Bungkus (Jurnal ILMU DASAR, 2020)
Aquifer in river bank area is mostly susceptive toward pollution occurring in river. One of parameters to determine the interaction process between groundwater and river is a natural isotope of 222Rn. The significant difference of radon concentration in groundwater and river water can be utilized as a scientific basis for investigating groundwater infiltration in river bank. Those studied parameters are residence time and infiltration rate. The research using 222Rn had been conducted in shallow groundwater of Ciliwung river bank - South Jakarta during rainy and dry season. The range of 222Rn concentration in shallow groundwater monitored in dry season was between 666 - 2590 Bq/m3 which was higher than that of rainy season ranging at 440 to 1546 Bq/m3. Otherwise, concentration of 222Rn in river water could not be detected (its 222Rn concentration = 0 Bq/m3) due to its much lower concentration either rainy or dry season. During dry season monitoring, equilibration between groundwater and river water was reached at the distance approximately 98 - 140 m away from river side. Estimating residence time based on 222Rn concentration at nearest site from the river and at equlibration area was 4.2 days such that the infiltration rate from river water into aquifer might be 7.8 m/day.Keywords: 222Rn, groundwater, residence time, infiltration rate.